Determination of flood zones with HEC-RAS in zones of the Central Andes mountain range. Microcuenca Saraus-La Llanga river. Celendin - Alcántara Boza, Alejandro (2021)
Floods are a seasonal phenomenon that occurs in spaces with occasional storms and influenced by topographic characteristics of the terrain. There are few studies of flood zones in the Andes Mountains, therefore in this study hydraulic simulation models were used to identify risk and disaster areas. Hec-Ras is a hydrological flood model used for unstable flows, and under return periods of 30, 50 and 100 years for stable flows, in the micro-basin of the Saraus River. The model uses differential equations of the deterministic type that allow us to forecast the dynamics of water levels due to extreme hydrometeorological events. Various geospatial tools were used such as HEC-RAS, RasMapper, geometric TIN data obtained from a digital elevation model (DEM / SRTM), satellite images and Geographic Information Systems. For the hydraulic simulation, 26 cross sections were trace 300 meters apart. The simulated stains of annual river floods provide information on the effect of flooding for three return periods of 30, 50 and 100 years. The risk areas with the greatest impact from floods correspond to the beginning of the basin, reaching heights of up to 10 m with widths of up to 140 m. Some areas are destined for agricultural activities, which generates losses of crops mainly and economic losses and even human lives, which in many cases goes unnoticed due to lack of information and management in high mountain watersheds.